Carl Nielsens ‘Maskarade’ og Det Kongelige Teaters scenemusik til Holbergs komedier - Foltmann, Niels Bo (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
Niels Bo Foltmann: Carl Nielsen’s ‘Masquerade’ and the Royal Theatre’s stage music for Holberg’s comedies. The article examines the relationship between Carl Nielsen’s opera Masquerade (1906) and the opera’s literary precedent – Ludvig Holberg’s comedy Masquerade (1724), and the stage music for the comedy, which had been used at the Royal Theatre before the opera’s creation and for some 10 years after its first performance. Not surprisingly, Carl Nielsen made use of the references to music that appear in Holberg’s comedies, particularly references to various pieces of dance music, such as Magdelone’s dance scene in the first act and the Dance of the Cockerel in the third act. The author also illustrates how it is highly likely that Carl Nielsen was aware of the traditional stage music for Holberg’s comedies and, on this background, makes a comparison of various compositions from the stage music and the corresponding section in the opera. It thus appears that, in several passages, the composer worked within a musical tradition – this applies especially to the overture, to the Dance of the Cockerel and to various dance-like passages in the third act. In several instances, Carl Nielsen adopted a musical idea or motif and transformed it into his own personal style. The extent to which the composer consciously adopted the Holberg music is not clear. He apparently wanted to create a Holberg tone or, perhaps, this style simply “flowed from his pen” since he must have been very familiar with this repertoire. The former was most likely the case, and we can imagine that the references to the stage music perhaps were thought of as a teasing, humorous salute to musical colleagues in the orchestra and to an audience that was already familiar with traditional Holberg stage music.